Murder from A to Z - Burns, V. M., 1964- (Burns, V. M., 1964- Mystery bookshop mystery, 2026)
When Michigan bookshop owner and mystery writer Samantha Washington and her sister, Jenna, agreed to host a class for seniors on estate planning, they didn't plan on discovering shady doings at Shady Acres Retirement Village . . . Nana Jo has volunteered her lawyer granddaughter, Jenna, to teach estate planning to retirees--with Sam providing her bookshop as the venue. But during the seminar, entitled Getting Your Ducks in Order, it quickly becomes clear someone's up to Fowl Play. When elderly Alva Tarkington, accompanied by her niece, sits down for a consultation, Sam realizes the woman's frequent blinking is actually Morse Code--S.O.S. The sisters get her alone, and Alva tells them she believes her life is in danger and must change her will . . . Unfortunately, Alva is found dead the next day--seemingly from natural causes. But Nana Jo and the sisters suspect otherwise. In between penning her latest historical mystery, set in 1939 as England declares war on Germany and Lady Elizabeth Marsh pursues stolen paintings and a traitor, Sam teams up with the senior sleuths of Shady Acres to search for motives--beginning with Alva's family. They soon learn not everyone is who they say they are, and someone is more than qualified to teach a class on cold-blooded murder . . .